THEMIS satellite observations of hot flow anomalies at Earth's bow shock - C. Chu; H. Zhang; D. Sibeck; A. Otto; Q. Zong; N. Omidi; J. P. McFadden; D. Fruehauff; V. Angelopoulos (Annales Geophysicae, 2017)
Hot flow anomalies (HFAs) at Earth's bow shock were identified in Time History of Events and Macroscale Interactions During Substorms (THEMIS) satellite data from 2007 to 2009. The events were classified as young or mature and also as regular or spontaneous hot flow anomalies (SHFAs). The dataset has 17 young SHFAs, 49 mature SHFAs, 15 young HFAs, and 55 mature HFAs. They span a wide range of magnetic local times (MLTs) from approximately 7 to 16.5 MLT. The largest ratio of solar wind to HFA core density occurred near dusk and at larger distances from the bow shock. In this study, HFAs and SHFAs were observed up to 6.3 RE and 6.1 RE (Earth radii), respectively, upstream from the model bow shock. HFA–SHFA occurrence decreases with distance upstream from the bow shock. HFAs of the highest event core ion temperatures were not seen at the flanks. The ratio of HFA ion temperature increase to HFA electron temperature increase is highest around 12 MLT and slightly duskward. For SHFAs, (Tihfa∕Tisw)/(Tehfa∕Tesw) generally increased with distance from the bow shock. Both mature and young HFAs are more prevalent when there is an approximately radial interplanetary magnetic field. HFAs occur most preferentially for solar wind speeds from 550 to 600 km s−1. The correlation coefficient between the HFA increase in thermal energy density from solar wind values and the decrease in kinetic energy density from solar wind values is 0.62. SHFAs and HFAs do not show major differences in this study.